1974
DOI: 10.1073/pnas.71.5.2108
|View full text |Cite
|
Sign up to set email alerts
|

Unique Double-Stranded Fragments of Bacteriophage T5 DNA Resulting from Preferential Shear-Induced Breakage at Nicks

Abstract: Nicks within one strand of the bacteriophage T5 DNA molecule act as "weak points" for a novel kind of mechanical breakage that can be utilized for "dissecting" the genome. The products from sheared T5+ DNA include five unique double-stranded segments of the molecule and various combinations of adjacent segments. These specific fragments are not obtained after repair of the nicks with DNA ligase (EC 6.5.1.1). The duplex fragments and most of their single-stranded components have been separated, identified, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 24 publications
(36 reference statements)
3
23
0
Order By: Relevance
“…One migrated with fragment 8 (Fig. 2), and the other migrated behind fragment 3. The alterations seen in the two BF23 deletion mutants were similar to those obtained with T5st mutants (6,17). The BF23st(102) deletion appeared to occur within the segment covered by fragments 7 and 12.…”
supporting
confidence: 69%
“…One migrated with fragment 8 (Fig. 2), and the other migrated behind fragment 3. The alterations seen in the two BF23 deletion mutants were similar to those obtained with T5st mutants (6,17). The BF23st(102) deletion appeared to occur within the segment covered by fragments 7 and 12.…”
supporting
confidence: 69%
“…Shearing of the DNA was performed either with G-tubes (Covaris®) or by passage through a small bore needle 37 to average size of 15 kbp to 40 kbp. The needle method was used during an evaluation of shearing techniques.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that double-strand breaks may be produced at sites of preexisting single-strand nicks by enzymes and shear forces (Hayward, 1974). To investigate the possibility that the observed double-strand breaks were artifacts of such action, E. coli AB2497 cells with about 6% thymine replaced by bromouracil were grown in aspartate medium to reduce the DNA content to < 1.3 genomes/cell.…”
Section: Nd = I Nsmentioning
confidence: 99%